Penerapan Model Pembelajaran Auditory Intellectually Repetition (Air) pada Pembelajaran IPA Kelas V SD - Ellensya Alvaringga; Aren Frima (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to be able to determine the complateness of social studies leaening outcomes in fifth grade student atSD Negeri Wukirsari. This research method is pre-experimental design. The population is all students of class V SD Negeri Wukirsari and the research sample totaling 26 students. The data collected was then analyzed using tests. Based on data analysis whith a confidence level of a = 5% and dk =25shows that Zcount = (6,98) Ztable = (1,64) then Zcount ≥ Ztable. Thus it can be concluded that the social studies learning outcomes of fifth grade student at SD Negeri Wukirsari after the application of the auditory intellectually repetition (AIR) learning model are significantly complete. Whit an average student final test score of 79.80 and the percentage of student who have completed as many as 24 student 92.30%. Thus, it can be concluded that the social studies learning outcomes of fifth grade students at SD Negeri Wukirsari after implementing the Auditory Intellectually Repetition (AIR) learning model are significant. Keywords: Application, Auditory Intellectually Repetition (AIR)